2021
DOI: 10.1007/s42452-021-04215-1
|View full text |Cite
|
Sign up to set email alerts
|

A remote sensing-based evaluation of channel morphological characteristics of part of lower river Niger, Nigeria

Abstract: River bank erosion, accretion and lateral channel migration are important geomorphological processes, which attract a great deal of attention of river engineering scientists in many parts of the world. The present study assesses the morphological characteristics of parts of the lower section of River Niger, where field data are scarce and difficult to access for security and cost implications. Multi-date (1990, 2002 and 2017) Landsat imageries were used for the study, the imageries were corrected for geometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The middle part of the river has seen to be more stable. Moreover, according to the study on lower part of river Niger ( Ibitoye, 2021 ), the nature of the river channel centerline was not constant both at the left and right flange of the river flow paths throughout the years as the centerline shifted towards the east in the earlier years of study (1990–2002) but migrated greatly in the later years of study (2002–2017) in the westward direction. They also found that the shifting of the bank line was abundant to eastwards at right flange and westwards at the left flange.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The middle part of the river has seen to be more stable. Moreover, according to the study on lower part of river Niger ( Ibitoye, 2021 ), the nature of the river channel centerline was not constant both at the left and right flange of the river flow paths throughout the years as the centerline shifted towards the east in the earlier years of study (1990–2002) but migrated greatly in the later years of study (2002–2017) in the westward direction. They also found that the shifting of the bank line was abundant to eastwards at right flange and westwards at the left flange.…”
Section: Resultsmentioning
confidence: 99%
“…Over all, it can be said that a maximum of width changes 10.21% was observed for 1993–98 (before construction of the Bridge) at F and increase of 12.14% at E, and the reduction of width changes was not significant for the year 2003–08 (after construction of the Bridge) but increasing of 15.55% at B was observed. According to the study on lower part of river Niger ( Ibitoye, 2021 ), the river channel width was showed diverse reduction and growth at various indicated sections of the channel reach.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, many international studies were carried out to identify the morphological and spatio-temporal pattern of the river planform and their bankline migration with the aid of GIS and remote sensing tools [13][14][15][16][17][18]. Remote sensing has been used by researchers for more than thirty years to investigate the surface of the earth [19], of which supervised remote sensing techniques have been widely used for the analysis of satellite images.…”
Section: Introductionmentioning
confidence: 99%